(untitled) (The International Journal for Scientific Research, 2025)
This analytical study aims to elucidate the eleven prophetic roles explicitly delineated in the Quranic text and illuminate their scientific and methodological significance in establishing an understanding of the Prophetic Sunnah as the practical embodiment and optimal application of Quranic guidance in the reality of human life. The study employs contemporary reformist methodology that emphasizes the functional integration between Quranic text and prophetic application), exploring the pivotal prophetic functions: recitation (tilawah), transmission (tabligh), clarification (bayan), counsel (nasiha), teaching (ta’lim), purification (tazkiyah), following (ittiba’), emulation (iqtida’), guidance (ihtida’), exemplification (ta’assi), and stewardship (haymanah). Through rigorous methodological analysis, the study reveals the integrative nature of these roles and their synergistic interaction in transforming theoretical Quranic principles into a comprehensive practical system for human conduct and societal organization. The findings confirm that the Prophetic Sunnah represents the highest and most comprehensive practical model of Quranic values, principles, and ethics, providing contemporary Muslim communities with an integrated reference framework for dealing with contemporary challenges while preserving authentic civilizational identity. The study contributes to enriching contemporary Islamic studies literature by presenting an integrative methodology that connects theoretical foundation with practical application, opening new horizons for research into the dialectical relationship between revelation and reality.